Factors influencing phagocytosis of malaria parasites : the story so far - Chua, Caroline Lin Lin (2021)
There are seven known species of Plasmodium spp. that can infect humans. The human host can mount a complex network of immunological responses to fight infection and one of these immune functions is phagocytosis. Effective and timely phagocytosis of parasites, accompanied by the activation of a regulated inflammatory response, is beneficial for parasite clearance. Functional studies have identified specific opsonins, particularly antibodies and distinct phagocyte sub-populations that are associated with clinical protection against malaria. In addition, cellular and molecular studies have enhanced the understanding of the immunological pathways and outcomes following phagocytosis of malaria parasites. In this review, an integrated view of the factors that can affect phagocytosis of infected erythrocytes and parasite components, the immunological consequences and their association with clinical protection against Plasmodium spp. infection is provided. Several red blood cell disorders and co-infections, and drugs that can influence phagocytic capability during malaria are also discussed. It is hoped that an enhanced understanding of this immunological process can benefit the design of new therapeutics and vaccines to combat this infectious disease.